Disorders in the Mother-Placenta-Fetus System and their Role in the Development of Fetal Growth Restriction Syndrome - Aslonova M. J. (Scientific Trends, 2024)
The article presents the effectiveness of doppler imaging for assessing blood flow in large vessels, including the umbilical, uterine artery and middle cerebral artery. 90 women were examined in the second trimester, and 45 women showed signs of fetoplacental insufficiency, such as fetal growth restriction syndrome at 28-34 weeks. The study of utero-placental-fetal blood flow allows timely detection of early signs of a violation in the fetoplacental system and its timely correction.
Keywords: Fetal growth restriction syndrome, dopplerometry, middle cerebral artery, umbilical artery.